A Systematic Literature Review: The Role of Digital Technology in Improving Conceptual Understanding and Problem-Solving Skills - Yuanda Oktrin Lay; Inayah Wulandari; Sri Andayani (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
In response to the evolving demands of 21st-century education, particularly the critical need to enhance students' conceptual understanding and problem-solving skills in mathematics, the strategic integration of digital technology has become increasingly vital. This research aims to explore the role of digital technology in improving students' conceptual understanding and problem-solving skills by classifying the types of tools used in previous studies. The method employed is a Systematic Literature Review (SLR). Data were sourced from the Google Scholar database, collected, filtered, and synthesized to form an article. The results of this study indicate that digital technology plays a significant role in students' conceptual understanding and problem-solving abilities in mathematics. The digital tools and products used to enhance students' conceptual understanding in mathematics include Microsoft Teams, Microsoft Form, Nearpod, Kahoot, Construct 2, Geoshape, Miro, Teams Room, Google Docs, Quizizz, Wordwall, FlipPDF, Patt_Art, digital LKPD (Learning Activity Sheets), Digital Games-Based Learning (DGBL), and learning materials based on Internet Technology. Meanwhile, the tools and digital products used to improve students' problem-solving skills in mathematics include Liveworksheet, GeoGebra, Spreadsheet, Schoology, Edmodo, Cloud Technology (Google Docs, Google Slides, Google Drive, Google Meet, Google Classroom, and SlideShare), Desmos, Padlet, digital book media, digital LKPD, and digital games. Future research could explore more effective teaching strategies in utilizing digital technology, ensuring that it not only enhances conceptual understanding and problem-solving skills but also fosters students' independent learning.